Disability and Digital Media: a Marxist Criticism of Commodification in Digital Media Capitalism - MAKI, Ahmad (PT Batara Swastika Harati, 2025)
This study analyzes the commodification of disability in digital capitalism through Tokopedia, Alfamart, and Rexona campaigns on the YouTube platform. This study aims to identify how digital media presents disability issues in capitalist narratives, how the commodification of disability life in the context of digital media reflects the principles of capitalism, and what impacts this commodification has on public awareness and the structural struggles of people with disabilities. Using the Marxist commodification theory, this study shows that narratives of inspiration and inclusion are often used to attract public attention and associate brands with positive emotions. At the same time, structural needs such as accessibility and systemic equality are ignored. The results of this study reveal that although these campaigns raise public awareness of disability issues, their focus tends to be on individual achievements rather than systemic challenges. In addition, this commodification risks reducing people with disabilities to symbolic tools for the company's commercial purposes. This study concludes that although campaigns like these have the potential to change public perceptions, their contribution to structural empowerment is still limited. This study is significant in opening up further discussions about digital capitalism, social representation, and the importance of a more sustainable approach to empowering people with disabilities.